Treatment with Tinospora cordifolia ameliorates prenatal stress and maternal separation-induced memory deficits by restoring amygdaloid neuronal architecture - Ashwini LS; Mohandas Rao KG; Kiranmai S Rai; Somashekar B Shetty; Guruprasad Rao; Padmanabha Udupa EG; Chinmay Ajit Suryavanshi (Journal of HerbMed Pharmacology)
Introduction: Tinospora cordifolia (TC) possesses antioxidative properties and has been shown to improve cognition. In this study, the effects of TC were investigated on prenatal vibratory stress, maternal separation-induced amygdala plasticity, and memory retention in pregnant rats and their neonates. Methods: Four experimental animal groups of pregnant Wistar rats were employed in this research, including normal & vehicle controls, the stressed group, which received 3 hours of vibratory stress/day, and the TC-treated group, which received 6 mg/kg TC before vibratory stress. The neonates born to these mothers were then subjected to maternal separation, followed by postnatal TC treatment. After 6 weeks, the animals were assessed to evaluate memory retention, serum cortisol levels, and neuronal structural changes in the amygdala. Results: Neonates exposed to prenatal vibratory stress and maternal separation entered the dark compartment more quickly during the retention test (P<0.001), indicating reduced memory retention. In contrast, the TC-treated groups showed longer latencies (P<0.001), suggesting improved memory retention. The TC-treated mothers and neonates had longer dendrites with more branching points and intersections (P<0.001). However, these dendrites underwent pruning, indicating a complex structural response to stress and TC treatment. Conclusion: The results indicate that TC exerts neuroprotective effects against prenatal vibratory stress and maternal separation and aids memory retrieval in rats by restoring amygdala neuronal damage.